Blood-based biomarkers of frailty in older patients with cancer - Akagunduz B.; Ergün Y.; Akagündüz D. D.; Akbaş N.; Akagündüz D.; KARAOĞLU A.; SOYSAL P. (My University, 2025)
Purpose of review This review aims to evaluate the current evidence on blood-based biomarkers for frailty detection in older cancer patients. It explores the potential of various biomarkers, including inflammatory markers and microRNAs (miRNAs), to serve as indicators of frailty and examines the limitations of existing studies. The review also highlights the need for further research to validate these biomarkers and improve their clinical applicability. Recent findings Recent studies have examined blood biomarkers associated with frailty in older cancer patients. Findings suggest that elevated granulocyte levels and lower macrophage-derived stem cells and regulatory T cells are linked to frailty. Inflammatory biomarkers such as interleukin-6 and specific miRNAs, as well as higher neutrophil-to-lymphocyte ratios, have also been identified as potential indicators of frailty. While these biomarkers show promise, no single marker has proven sufficient, and combining them may improve frailty detection. Further research is needed to validate their clinical usefulness in this population. Summary Blood-based biomarkers show potential for detecting frailty in older patients with cancer, but further research is needed, particularly beyond an inflammatory focus and with more robust study designs.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Yoğun Bakım; Hemşirelik; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Intensive Care; Nursing; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Clinical Medicine (Med); Clinical Medicine; Critical Care Medicine; Onkoloji (hemşirelik); Yoğun Bakım Tıbbı; Oncology (nursing); Critical Care and Intensive Care Medicine; blood-based biomarker; frailty; older patients with cancer